1995
DOI: 10.1089/neu.1995.12.1015
|View full text |Cite
|
Sign up to set email alerts
|

Severe Controlled Cortical Impact in Rats: Assessment of Cerebral Edema, Blood Flow, and Contusion Volume

Abstract: Controlled cortical impact (CCI) is a contemporary model of experimental cerebral contusion. We examined the cerebrovascular and neuropathologic effects of a severe CCI in rats. The utility of magnetic resonance imaging (MRI) for the assessment of contusion volume after severe CCI was also established. Severe CCI (3.0 mm depth, 4 m/sec velocity) to the left (L) parietal cortex was produced in anesthetized (isoflurane/N2O/O2), intubated, and mechanically ventilated male Sprague-Dawley rats (n = 58). Physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
111
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(128 citation statements)
references
References 22 publications
16
111
1
Order By: Relevance
“…The lumped constant has been shown to increase significantly after focal ischemia because of depletion of tissue glucose (Nakai et al, 1987). However, as described in our results and other studies, the CBF reduction associated with experimental trauma is generally above the ischemic threshold except in the contusion core (Yamakami and McIntosh, 1991;Bryan et al, 1995;Kochanek et al, 1995;Forbes et al, 1997;Ginsberg et al, 1997;Richards et al, 2001). Finally it should be noted that we have not attempted to control for any effect of differential exposure to anesthetic between the groups (3 hours exposure versus a brief exposure in the 3-hour and 24-hour injury groups, respectively).…”
Section: Methodological Considerationssupporting
confidence: 72%
See 1 more Smart Citation
“…The lumped constant has been shown to increase significantly after focal ischemia because of depletion of tissue glucose (Nakai et al, 1987). However, as described in our results and other studies, the CBF reduction associated with experimental trauma is generally above the ischemic threshold except in the contusion core (Yamakami and McIntosh, 1991;Bryan et al, 1995;Kochanek et al, 1995;Forbes et al, 1997;Ginsberg et al, 1997;Richards et al, 2001). Finally it should be noted that we have not attempted to control for any effect of differential exposure to anesthetic between the groups (3 hours exposure versus a brief exposure in the 3-hour and 24-hour injury groups, respectively).…”
Section: Methodological Considerationssupporting
confidence: 72%
“…Disturbances in cerebral blood flow (CBF are also a common sequela of head injury and have been documented both experimentally (Yamakami and McIntosh, 1991;Bryan et al, 1995;Kochanek et al, 1995;Forbes et al, 1997;Hendrich et al, 1999;Lythgoe et al, 2003) and clinically (Bouma et al, 1991;Marion et al, 1991;Martin et al, 1997;Coles et al, 2002). CBF abnormalities have been shown to be an important mechanism underlying secondary brain damage experimentally (Jenkins et al, 1989;Giri et al, 2000) and clinically have been shown to be strongly associated with poor outcome (Robertson et al, 1992).…”
mentioning
confidence: 99%
“…Multivariate analysis also revealed an effect of time after injury on CBF. Most investigators have reported an initial reduction in CBF, followed by progressive recovery after experimental TBI (Yamakami and McIntosh, 1989;Kochanek et al, 1995). In saline-treated rats in this study, after severe CCI, CBF recovered by B5% to 50% between B3.5 and B5 h in ROIs beneath the impact site.…”
Section: Effect Of 2-chloroadenosine On Cerebral Blood Flow After Trasupporting
confidence: 46%
“…In animal models of TBI, brain prostaglandin levels have been shown to rise rapidly postinjury (Ellis et al, 1989;Dewitt et al, 1988;Shohami et al, 1987). Prostaglandin changes in these studies seemed to be associated with brain injury itself; changes in cerebral blood flow following TBI rarely declined to levels associated with ischemia-induced prostaglandin increases (Obrist et al, 1984;Povlishock and Kontos, 1985;Kempski et al, 1987;Ellis et al, 1988;McIntosh, 1989, 1991;Bouma and Muizelaar, 1992;Muir et al, 1992;Kochanek et al, 1995;von Stück et al, 1996).…”
Section: Introductionmentioning
confidence: 98%